2008
DOI: 10.1007/s10157-007-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome in a patient with situs inversus totalis

Abstract: Situs inversus totalis is a rare congenital anomaly that often occurs concomitantly with other disorders. A spectrum of renal abnormalities of patients with situs inversus has been reported. Developmental anomalies, including agenesis, dysplasia, hypoplasia, ectopia, polycystic kidney, and horseshoe kidney, have been reported. The association of situs inversus with nephrotic syndrome is very rare. We report the first known case of situs inversus totalis with nephrotic syndrome caused by primary focal segmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although some cases of nephrotic syndrome in SI totalis patients have been reported, the mechanisms of renal dysfunction in adults with SI totalis are still unknown. Domański et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some cases of nephrotic syndrome in SI totalis patients have been reported, the mechanisms of renal dysfunction in adults with SI totalis are still unknown. Domański et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is often associated with congenital multiple organ anomalies; dysplasia and hypoplasia were previously reported in the kidney. Although nephrotic syndrome and renal amyloidosis have been reported in SI patients, the mechanisms of occurrences remain unknown owing to scarcity of cases. To our knowledge, KT surgery and postoperative course in an ESRD patient with SI totalis have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 Situs inversus totalis has been reported occasionally in adults with nephrotic syndrome, 5,6 probably owing to disturbed transforming growth factor b (TGFb) and Smad protein signalling, and the interaction of these molecules with vascular permeability factor (VPF) which is produced by T-cells. 5,6 Excess VPF produces changes in epithelial foot processes, leading to nephrotic range proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…This patient progressed to end stage renal failure (ESRD) and followed up under chronic hemodialysis treatment in contrast to our patient having normal renal functions. In the case by Vikrant et al [4], the etiology of the nephrotic syndrome in such a patient was found to be focal segmental glomerulosclerosis. In a different report [5], authors discussed a case of SI with steroid sensitive nephrotic syndrome and in conclusion they suggested that disturbed trans TGF-beta and Smad signaling could be responsible for both nephrotic syndrome and situs inversus totalis.…”
Section: Open Accessmentioning
confidence: 94%
“…Primary ciliary dyskinesia (PCD) and resultant situs inversus (SI) totalis are very rare anomalies characterized by the total inversion of all abdominal and thoracic organs and chronic bronchiectasis [1]. The association of SI totalis with nephrotic syndrome has been reported only four times so far in which focal segmental glomerulosclerosis and amylodiosis were the etiologic factors [2][3][4][5]. Herein we report a case of nephrotic syndrome and amyloidosis due bronchiectasis in a patient with SI to talis.…”
Section: Introductionmentioning
confidence: 99%